Search for the Higgs Boson in the H -> WW(*()) -> l(+)vl(-)(v)over-bar Decay Channel in pp Collisions at root s=7 TeV with the ATLAS Detector - Onofre, A. (2012)
A search for the Higgs boson has been performed in the H→WW(*)→ℓ+νℓ−¯ν channel (ℓ=e/μ) with an integrated luminosity of 2.05  fb−1 of pp collisions at √s=7  TeV collected with the ATLAS detector at the Large Hadron Collider. No significant excess of events over the expected background is observed and limits on the Higgs boson production cross section are derived for a Higgs boson mass in the range 110  GeV<mH<300  GeV. The observations exclude the presence of a standard model Higgs boson with a mass 145<mH<206  GeV at 95% confidence level.